A Review of Interleukin-23/Interleukin-17 Inhibitor Exposure during Pregnancy in Patients with Psoriasis - Nirali Doshi; Bijal Prajapati; Lavanya Selvaraj (Wolters Kluwer Medknow Publications, 2024)
Psoriasis is an immune cell-mediated chronic relapsing inflammatory skin disease that often develops during the reproductive years of women. The treatment of psoriasis during pregnancy is challenging as remarkable changes occur in the maternal body, and it requires the selection of therapy which is safe for both mother and fetus. The use of interleukin-23 (IL-23)/IL-17 inhibitors has been growing in psoriasis disease management and so the risk of their exposure during pregnancy is increasing too. However, human safety data in pregnancy are limited. This article aims to review pregnancy outcomes associated with IL-23/IL-17 inhibitor exposure in psoriasis patients and to see possible therapeutic options for psoriasis treatment during pregnancy. A search of the PubMed database up to June 2023 for articles was performed. The search strategy included a combination of terms as (pregnancy) AND (psoriasis) AND (Ustekinumab)/(Secukinumab)/(ixekizumab)/(brodalumab)/(guselkumab)/(tildrakizumab)/(risankizumab)/IL-23 inhibitors/IL-17 inhibitors. Resulted articles were reviewed manually for case reports, exposures from registries, and clinical trials. Most of the exposures to IL-23/IL-17 inhibitors were inadvertent, and therapy was suspended upon the detection of pregnancy. No signals on miscarriages, spontaneous abortions, and adverse developmental outcomes have been reported with first-trimester exposures to IL-23/IL-17 inhibitors. However, benefit-risk profile cannot be extrapolated based on first-trimester exposure as the transfer of these biologics across the placenta occurs in the later stage of pregnancy. More safety data from large cohorts of full-term exposure are required for IL-23/IL-17 inhibitors to consider them safe therapeutic options during pregnancy.